(untitled) (Research, Society and Development, 2020)
This article aims to discuss the unitary knowledge and the pragmatic relationship of man and nature as an obstacle to the formation of the scientific spirit in the view of Gaston Bachelard and the challenges of contemporary science. Dogmas, generalities and preconceptions without scientific evidence constitute obstacles to achieving scientific progress. Based on these obstacles, it situates the challenges that contemporary science faces. In methodological terms, it is a bibliographic research and is based on the interpretation of qualitative data based on the epistemological obstacles that immobilize the formation of the scientific spirit. It is understood that unitary knowledge makes the investigation of particular phenomena impossible and that the pragmatic explains the phenomena from the utility they bring to man, being problematized by Gaston Bachelard as an obstacle to the formation of the scientific spirit. Bachelard’s assumptions are considered to propose a new approach to the conception of epistemology, pointing to a new meaning in the dialectical method of production and systematization of the scientific process. It is evident in the study that the development of science was and still is influenced by the culture of its time.